PENGGUNAAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPS DI SEKOLAH DASAR - Rahardi, Dwi Ibnu; Marini, Arita; Yunus, Muhammad (Cahaya Ilmu Bangsa Institute, 2024)
This study aims to reanalyze the use of audio-visual media on the learning outcomes of Social Studies in Elementary Schools. Research with the title